2023
DOI: 10.1038/s41375-023-01853-9
|View full text |Cite
|
Sign up to set email alerts
|

KDM6B protects T-ALL cells from NOTCH1-induced oncogenic stress

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematopoietic neoplasm resulting from the malignant transformation of T-cell progenitors. While activating NOTCH1 mutations are the dominant genetic drivers of T-ALL, epigenetic dysfunction plays a central role in the pathology of T-ALL and can provide alternative mechanisms to oncogenesis in lieu of or in combination with genetic mutations. The histone demethylase enzyme KDM6A (UTX) is also recurrently mutated in T-ALL patients and functions as a tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…3 B). A previous study highlighted KDM6B ’s crucial role in supporting NOTCH1 -driven T cell acute lymphoblastic leukemia [ 40 ]. The synergistic effect of NOTCH1 and KDM6B mutations therefore may accelerate lymphoma progression by activating oncogenic pathways via chromatin remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…3 B). A previous study highlighted KDM6B ’s crucial role in supporting NOTCH1 -driven T cell acute lymphoblastic leukemia [ 40 ]. The synergistic effect of NOTCH1 and KDM6B mutations therefore may accelerate lymphoma progression by activating oncogenic pathways via chromatin remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, KDM6B is required to prevent apoptosis of NOTCH1-driven T-ALL. Therefore, targeting KDM6B might be an efficient therapeutic strategy for NOTCH1-induced T-ALL patients [ 29 ]. Other studies showed that transgenic deletion of interleukin-15 (IL-15) or IL-15 receptor alpha-chain generates T-ALL in NOD mice accompanied by increased NOTCH1 activation and impaired DNA repair capability.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently suggested that this effect relies on 'metabolic reservoirs' [40], which represent a pool of vital metabolites ready to be used by cancer cells. It has been reported that the Warburg effect in cancer cells generates an antiapoptotic extracellular microenvironment by elevating the extracellular lactate/pyruvate ratio, which desensitizes HepG2 cells toward apoptotic insult [41]. Indeed, dynamic metabolic changes characterize the heterogenous responses of Jurkat, TALL1, and the NOTCH-independent Loucy cells under a TEC-conditioned medium.…”
Section: Discussionmentioning
confidence: 99%